2021
DOI: 10.22159/ijap.2021v13i4.41931
|View full text |Cite
|
Sign up to set email alerts
|

Design of Controlled Release Mucoadhesive Buccal Tablets of Ivabradine HCL Using Sintering Technique

Abstract: Objective: The objective of the present work was to study the use of the sintering technique, a relatively new concept in pharmaceutical sciences, in the development of mucoadhesive buccal tablets for ivabradine Hydrochloride. Methods: The method consisted of blending drug, hydroxypropyl methylcellulose (HPMC K100M), carnauba wax, and other excipients followed by direct compression into tablets. The compressed fluffy matrices were sintered at two different constant temperatures like 50 °C and 60 °C for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The results of the study showed that the developed tablets had excellent mechanical and floating properties, with controlled drug release properties. The use of the sintering technique in tablet preparation significantly affected the drug release properties of the tablets, and the drug-polymer ratio, sintering temperature, and duration could be optimized to achieve desired drug release properties for specific drug delivery applications [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that the developed tablets had excellent mechanical and floating properties, with controlled drug release properties. The use of the sintering technique in tablet preparation significantly affected the drug release properties of the tablets, and the drug-polymer ratio, sintering temperature, and duration could be optimized to achieve desired drug release properties for specific drug delivery applications [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa was attached to the glass piece and a tablet attached to the hanging thread. The balance was adjusted so that the hanging side was 5 g heavier and the force required to detach the tablet was measured [19].…”
Section: In Vitro Mucoadhesion Testmentioning
confidence: 99%
“…Stability studies were performed on the optimized batch according to ICH guidelines. Samples were stored at 40°C/75% RH for 3 months [19,24]. Samples were evaluated after each month for hardness, drug content and in vitro drug release.…”
Section: Stability Studiesmentioning
confidence: 99%